Community biodiversity management : promoting resilience and the conservation of plant genetic resources - Boef, Walter de. (Abingdon [England] : Routledge, 2013)
"The conservation and sustainable use of biodiversity in the environments where this diversity originated or is being used, are issues which are high on the policy agenda. This book is the first to set out a clear overview of community biodiversity management (CBM) as an approach to meet social, economic and environmental change"--
pt. 1. Community biodiversity management and in situ conservation -- pt. 2. Practices contributing to community biodiversity management -- pt. 3. People, biodeversity and landscapes -- pt. 4. Agrobiodiversity, livelihoods and markets -- pt. 5. Participatory crop improvement in a context of community biodiversity management -- pt. 6. Community biodiversity management, genetic resource policies and rights -- pt. 7. Community biodiversity mangement and resilience.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Biodiversity conservation -- Citizen participation; Sustainable agriculture -- Citizen participation; Plant genetics; Electronic books